Monitoring Sand Encroachment on Highways in the Qassim Region Using Remote Sensing and Geographic Information Systems - Al-Omar, Fidaa Sulaiman; Al-Dughairi, Mohammed Ibrahim (Journal of natural sciences, life and applied sciences, 2025)
Sand encroachment is one of the most prominent environmental challenges affecting the infrastructure of land roads in the Kingdom of Saudi Arabia, as it leads to traffic disruption and increased accidents. The highways connecting Al-Qassim with Hail, Al-Qassim with Riyadh, and Al-Qassim with Al-Madinah Al-Munawarah are exposed to varying degrees of sand encroachment. This study aims to employ remote sensing RS and geographic information systems GIS to monitor and analyze sand encroachment along these roads during the period from 2014 to 2024, and to identify the most threatened areas, and propose effective solutions to reduce the impact of the phenomenon on the roads. The study adopted several scientific methodologies, including the spatial analytical method to monitor the geographical distribution of the phenomenon, the mathematical method to measure the spectral indices (NDSI, NDVI, BSI), the historical method to track temporal changes, and the descriptive analytical method to analyze the differences between the roads. The results revealed a relative decrease in the spread of sand dunes and soil exposure during the period from 2014 to 2024. Where the NDSI values ranged between (–0.43 to 0.70) in 2014, and decreased to (–0.51 to 0.55) in 2024, indicating a decrease in the extent of sand dune spread. BSI values also decreased from (–0.04 to 0.64) to (–0.01 to 0.58), indicating a decrease in the degree of soil exposure. The results showed that the Al-Qassim Riyadh road is the most affected, followed by the roads to Hail and Al-Madinah, and that the areas with low vegetation cover recorded the highest rates of sand encroachment. Areas that witnessed a significant increase in encroachment included Nafud Al-Sir and Al-Quwara, compared to more stable areas such as the Jabal Tumayyah area. In light of these results, the study recommends planting vegetation barriers on both sides of the highways, especially in areas with weak vegetation cover, establishing mechanical barriers in the areas most affected by sand encroachment, and implementing regular monitoring programs using remote sensing and geographic information systems to track sand movement and take appropriate preventive measures.
Keywords: sand encroachment; highways; Qassim; NDSI; BSI; NDVI